Vision Screening Programmes: Collaborative work for developing evidence-based vision screening protocols. - Strang, Niall; Barrett, Brendan; Baraas, Rigmor C (Scandinavian Journal of Optometry and Visual Science, 2021)
This editorial highlights the scope of the topic that need to be examined further in the field of children’s vision screening. We hope that by making vision screening a special topic in SJOVS we can encourage collaboration between groups of researchers, clinicians and students and help in the development of evidence-based solutions to the current problems facing vision screening across the world. Of course, identifying eye and vision problems represents only the first stage in a screening process. It is important to mention that any screening programme requires several follow up steps to be successful. Good access to further examination for screening is required and affordable spectacles need to be provided. A mechanism of follow up is also important as, once dispensed, the spectacles need to be worn appropriately. Failure to address any of these issues will limit the benefits of a screening programme and innovative methods of addressing these issues are encouraged.